The impact of social media and smartphone use on the relation between the users and the news in Turkey - Bilgici, Ceren (Istanbul Kultur Univ, Atakoy Campus, Bakirkoy, Istanbul, 34156, Turkey, 2016)
In this article, the experiences of the users with regard to the development of new technologies (of telecommunication, internet and cellphones) in Turkey on the internet are analyzed. The objective is to demonstrate the effects of the new technologies on the practices of the internet users reaching the news via cellphone. The purpose is to observe the transformation of the daily practices on the Internet due to the evolution of the broadband, the development of the telecommunication market, the development of the adapted interface to the website ergonomics and the invention of the new technological devices such as smartphones. The aim of this study is to find out the new ways of searching news via mobile phones. We analyzed the relation between Turkish users and new information and communication technologies and the transformation of the habits of searching news and the role of social media platforms in this subject. According to our studies, the digitalization of the news, evolution of smartphones and the development of social media affect the habits and manners of reading, searching and sharing news. Nowadays, the practices of online news consumption are multiple. The interface ergonomics of websites and applications has a significant role on the media preferences of the users.
Keywords: Social Media; Internet; Smartphone; Online Journalism; Interface Ergonomics